Pengaruh Employer Branding Terhadap Minat Melamar Kerja Di PT.Telekomunikasi Indonesia Kota Medan - Yohannes Manao; Kevin Samuel Benammi Sembiring; Muhammad Daffa Aqila; Anggiat Faisal Butar Butar; Risky M Soleh; Onan Marakali Siregar; Afrila Mulyati Siregar (CV. ITTC INDONESIA, 2024)
This study discusses the concept of employer branding and its impact on job application interest at PT Telkom Indonesia Regional Office I Sumatra. Employer branding is defined as a package of economic and psychological functions offered by a company according to the jobs provided, with the main goal of building a company's image that cares about the interests and needs of employees. Key aspects of employer branding include developing the company's value proposition, external recruitment, and employee engagement in organizational culture. Job application interest is the process of someone's interest in a job, starting from searching for information about job vacancies, selection, and decision-making to apply to a particular company. This study found that employer branding positively influences job application interest at PT Telkom, especially among millennials who are accustomed to technology and more responsive to job promotions through social media. These findings support previous research indicating that employer branding has a positive impact on job application interest. Future studies are recommended to continue monitoring changes in technology and market trends, as well as retesting to evaluate opinions and process adjustments that may be needed. Thus, this research provides an important contribution to understanding the importance of employer branding in attracting potential employees and retaining existing employees at PT Telkom Indonesia Regional Office I Sumatra.